ASSESING THE EFFECT OF IBL ON MATHMETICS UNDERSTANDING AT JUNIOR HIGH SCHOOL LEVEL - Syahgita, Najwa; Nurramadhani, Nesya; Rizki, Zaki Yazidatur; Wahyunengsih (Relevan : Jurnal Pendidikan Matematika, 2025)
This study aims to evaluate the impact of the Inquiry-Based Learning (IBL) approach on students’ understanding, motivation, and engagement in mathematics at junior high school level. IBL is a learning method that emphasizes the active involvement of students through questioning, investigation, and problem-solving, which is based on the theory of constructivism developed by Piaget and Vygotsky. This study used a descriptive quantitative survey method involving 39 junior high school students as respondents, using a questionnaire as a data collection instrument distributed online through Google Forms. The analysis showed that most students gave a “Strongly Agree” response to the effectiveness of IBL, especially in facilitating understanding of mathematical concepts, increasing participation in group discussions, and motivating them to learn. 97.3% of students stated that it was easier to understand mathematics material after participating in experimental or investigative activities. In addition, this approach was also proven to encourage increased self-confidence, independent learning ability, and critical thinking and problem-solving skills. These findings confirm that IBL is a practical approach relevant to constructivist learning principles. Therefore, it is recommended that mathematics teachers apply IBL in teaching and learning activities with appropriate assistance and integrate it consistently into the learning process.